COMPARATIVE ANALYSIS BETWEEN THE INCOME OF ITINERANT FISH TRADERS AND SEDENTARY FISH TRADERS IN OESAPA MARKET, KUPANG CITY - Heni Sauw; Reisanty Djami; Maisy Bori (SEAN Institute, 2023)
The objectives of this study are (1) to determine the amount of income of itinerant fish traders and sedentary fish traders in Oesapa market, Kupang City and 2) to determine the results of a comparative analysis of the income of itinerant fish traders and sedentary fish traders in Oesapa Market, Kupang City. The data collection method in this research is survey method. The method of taking samples in this study uses the method of Disproportionitstratifidrendom sampling which aims to make the samples compared equal. The sample taken in this study was a total of 8 people, 4 people each for itinerant fish traders and 4 people for sedentary fish traders. The data analysis technique used was the method of analyzing total cost (TC), revenue (TR), and income (π) from each itinerant fish trader and sedentary fish trader. The results of research showed that the income of sedentary fish traders is greater than the income of itinerant fish traders in Oesapa Market, Oesapa Village, Kupang City.